Technical Competence Achievement and Students’ Perceptions of Problem-Based Learning and Collaborative Learning in Electrical Circuit Instruction Among Vocational High School Students - Risqy Pratama Efendy; I Made Wirawan (FKIP - Universitas Riau, 2026)
Electrical circuit learning in vocational high schools requires a balance between theoretical understanding and practical skills to develop workplace relevant competencies. This study aimed to describe students’ technical competence achievement and their perceptions of the implementation of Problem Based Learning (PBL) and collaborative learning in electrical circuit instruction. A quantitative descriptive approach was employed involving 69 tenth grade students enrolled in the Electrical Power Installation Engineering program at SMK Negeri 1 Blitar. Data were collected using a 24 item Likert scale questionnaire and analyzed using descriptive statistics, including mean scores, frequencies, percentages, and Cronbach’s Alpha reliability testing. The findings indicated that students demonstrated high levels of technical competence across all evaluated indicators, with the highest mean score observed in the operation of electrical measuring instruments (M = 3.36). Students also reported positive perceptions of practice based learning (M = 3.30) and collaborative problem solving activities (M = 3.29). The instrument demonstrated acceptable reliability (Cronbach’s Alpha = 0.774). The findings describe students' technical competence achievement and perceptions during the implementation of PBL and collaborative learning and do not indicate causal effects or learning improvement.